PROYEKSI PRODUKSI DAN PERMINTAAN JAGUNG, PAKAN DAN DAGING AYAM RAS DI INDONESIA (Projections of Maize, Feed and Chicken Meat Production and Demand in Indonesia) - KETUT KARIYASA; BONAR M. SINAGA; M.O. ADNYANA (SOCA: Jurnal Sosial Ekonomi Pertanian, 2004)
Assessment on “Projections of Maize, Feed and Chicken Meat Production andDemand in Indonesia is focused to analyze a balance between the domesticproduction and demand for the next ten years, as well as to analyze its levelresponse to influence factors.This research used the national time series data for1980 to 2001 period. The econometric model (simultaneous regression) approachthrough the two stage least squares (2SLS) method had been implemented in orderto reach the objectives of this research. The projection results shown that ontechnology level and policies unchanged, the domestic production from thosecommodities until 2010 year are predicted not sufficient to meet its demand, so thattargeting for the maize and chicken meat self-sufficient in 2005 can not be reach. It isbetter, if effort to increase of the corn domestic production is more prioritized onimprovement of the technology aspect, because corn productivity is more responseto this aspect than to the other ones. The feed production and demand that weremore response to the maize price than to the feed price, and also the chicken meatproduction and demand that were more response to the chicken meat price itselfthan the feed price proofed that the feed market structure in Indonesia tend is closeto oligopoly market structure.